Intrapersonal conflict as the factor of professional self-determination - Andrey Georgievich Bolshakov, Victoria Ravilꞌevna Sagitova, Andrey Valeryevich Ivanov, (Opción, 2019)
The purpose of this work is to cover the issue of intrapersonal conflicts as the manifestations of profession internal choice in the process of professional self-determination via comparative qualitative research methods. As a result, there are conflicts between the need for independence and custody, as well as between the level of claims and achievements among the girls. In conclusion, the stage of choosing a profession at the level of an individual is intense, partly abstract in its manifestations.